Energy efficient routing protocols for wireless sensor networks: Comparison and future directions - Badlishah, Ahmad; Loganathan, M; Sabapathy, T; Ghazali, N.H; Nasrun Osman, M (2017)
Wireless sensor network consists of nodes with limited resources. Hence, it is important to design protocols or algorithms which increases energy efficiency in order to improve the network lifetime. In this paper, techniques used in the network layer (routing) of the internet protocol stack to achieve energy efficiency are reviewed. Usually, the routing protocols are classified into four main schemes: (1) Network Structure, (2) Communication Model, (3) Topology Based, and (4) Reliable Routing. In this work, only network structure based routing protocols are reviewed due to the page constraint. Besides, this type of protocols are much popular among the researchers since they are fairly simple to implement and produce good results as presented in this paper. Also, the pros and cons of each protocols are presented. Finally, the paper concludes with possible further research directions.